2006
DOI: 10.1634/stemcells.2006-0201
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow‐Derived Cells Contribute to Podocyte Regeneration and Amelioration of Renal Disease in a Mouse Model of Alport Syndrome

Abstract: In a model of autosomally recessive Alport syndrome, mice that lack the ␣3 chain of collagen IV (Col4␣3 ؊/؊ ) develop progressive glomerular damage leading to renal failure. The proposed mechanism is that podocytes fail to synthesize normal glomerular basement membrane, so the collagen IV network is unstable and easily degraded. We used this model to study whether bone marrow (BM) transplantation can rectify this podocyte defect by correcting the deficiency in Col4␣3. Female C57BL/6 Col4␣3 ؊/؊ (-/-) mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
5
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(161 citation statements)
references
References 38 publications
8
145
5
3
Order By: Relevance
“…Nevertheless, BM transplantation can improve renal function. Whole BM transplantation has been reported to be able to improve renal function and reduce histological damage in the collagen4α3 defective model of Alport syndrome [24,25]. These authors reported that BM-derived cells transdifferentiated into podocytes and mesangial cells, accompanied by re-expression of the defective collagen chains and improved renal histology and function.…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, BM transplantation can improve renal function. Whole BM transplantation has been reported to be able to improve renal function and reduce histological damage in the collagen4α3 defective model of Alport syndrome [24,25]. These authors reported that BM-derived cells transdifferentiated into podocytes and mesangial cells, accompanied by re-expression of the defective collagen chains and improved renal histology and function.…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms by which MSCs ameliorate I/R injury are not clear. Several studies have demonstrated the capacity of MSC to differentiate into kidney cells [11][12][13][14]. Controversial studies indicated that the grafted MSCs were not the predominant cellular components involved in the regeneration of injured tubuli [7,59], and it has been postulated that, rather than differentiation, cell fusion accounts for these cells [7,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MSCs can ameliorate renal ischemia/ reperfusion (I/R) injury [5][6][7][8][9][10]. It has been reported that MSCs repair renal damage by differentiating into tubular epithelial cells [11], mesangial cells [12], endothelial cells [13], and podocytes [14], and by producing renotrophic cytokines and growth factors [15][16][17][18][19]. For example, MSCs can produce insulin growth factor-1 (IGF-1) and hepatocyte growth factor (HGF) [15], both of which are renal-protective or renotrophic factors [18,19].…”
Section: Introductionmentioning
confidence: 99%